Embedding Local Wisdom in Joyful Mathematics Learning to Strengthen Early-Grade Numeracy: Evidence from the GEMBIRA Approach - Salmia; Abdul Malik (Journal of Local Wisdom in Education, 2025)
Mathematics learning in early primary grades is often perceived as abstract and difficult when classroom instruction is weakly connected to children’s cultural and everyday experiences. This condition can suppress engagement and contribute to low foundational numeracy achievement. To address this urgency, the present study examined the effectiveness of the GEMBIRA approach—an instructional model that integrates joyful learning principles with local wisdom—on improving Grade 2 students’ calculation skills. The research employed a mixed-methods design using a one-group pretest–posttest framework involving 23 purposively selected students, complemented by qualitative inquiry through classroom observations and semi-structured interviews with students, teachers, and parents. Quantitative data were collected using calculation tests and analyzed with descriptive statistics and paired-sample t-tests, while qualitative data were analyzed thematically to explain learning processes and participant perceptions across the GEMBIRA stages (dig and explore, load content, create activity, follow students’ thinking, celebrate, and end with appreciation). Results showed a statistically significant increase in calculation performance, with mean scores improving from 57.39 (pretest) to 83.91 (posttest) (p < 0.05). Qualitative findings indicated heightened motivation, more active participation, and clearer conceptual understanding when calculation tasks were embedded in culturally familiar narratives, practices, and traditional games, supported by teacher responsiveness to students’ thinking and structured appreciation. The novelty of this study lies in the systematic integration of local wisdom and joyful learning within a staged, classroom-ready model empirically evaluated in early-grade mathematics. In conclusion, culturally grounded, enjoyable instruction can strengthen foundational calculation skills. This study contributes a replicable framework that bridges ethnomathematics and practical pedagogy to advance the field of local wisdom in education.